2016
DOI: 10.1007/s10545-016-9993-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of ataxia phenotype in a new mouse model of galactose‐1 phosphate uridylyltransferase (GALT) deficiency

Abstract: Despite adequate dietary management, patients with Classic Galactosemia continue to have increased risks of cognitive deficits, speech dyspraxia, primary ovarian insufficiency, and abnormal motor development. A recent evaluation of a new galactose-1 phosphate uridylyltransferase (GALT)-deficient mouse model revealed reduced fertility and growth restriction. These phenotypes resemble those seen in human patients. In this study, we further assess the fidelity of this new mouse model by examining the animals for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Moreover, the clinical findings in our zebrafish model are in line with observations in other animal models for classic galactosemia. GALT-deficient flies exhibited motor impairments (Kushner et al 2010 ), whereas GALT-deficient mice exhibited brain abnormalities, and females showed a smaller litter size and longer time to achieve pregnancy (Chen et al 2017 ; Tang et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the clinical findings in our zebrafish model are in line with observations in other animal models for classic galactosemia. GALT-deficient flies exhibited motor impairments (Kushner et al 2010 ), whereas GALT-deficient mice exhibited brain abnormalities, and females showed a smaller litter size and longer time to achieve pregnancy (Chen et al 2017 ; Tang et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Animal models for classic galactosemia that tried to mimic the biochemical and clinical human phenotype(s) have been developed, a fruit fly (Kushner et al 2010 ) and two mouse models (Leslie et al 1996 ; Tang et al 2014 ), which have shown their value (Balakrishnan et al 2016 ; Chen et al 2017 ; Daenzer et al 2016 ; Jumbo-Lucioni et al 2013 , 2014 , b , 2016 ). We have created a zebrafish model for classic galactosemia that complements these models.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the only wholeorganism mammalian model-a GALT-null mouse-was created twice by separate investigators 11,12 and in one instance showed no relevant phenotypes 11 and in the other was reported to show some phenotypes, but these were pronounced only following extraordinary dietary galactose intoxication. 12,13 To explore the relationship between metabolites and outcomes, we created and characterised an outbred GALT-null rat model of CG. As demonstrated here, our GALT-null rats exhibit a range of phenotypes reminiscent of CG in humans, including cataracts, mild growth delay, and both cognitive impairment and motor deficits in adults.…”
mentioning
confidence: 99%
“…Furthermore, an increased abundance of BiP was found in this tissue. 61,62 Decreased thicknesses of the molecular and granular layer in the cerebellum of mutant mice suggested cerebellar hypoplasia. These mice manifested ataxia-related motor impairments with varying degrees of severity.…”
Section: Galt Deficiencymentioning
confidence: 99%
“…A progressive nature of the impairments in older mice was observed. 62 Additionally, studies by Balakrishnan et al showed down-regulated of the PI3/Akt pathway in isolated GALT-deficient ovaries. pAkt (Ser473), pGsk3β, and Hsp90 levels in the isolated GALT-deficient ovaries were significantly reduced and higher levels of BiP were found.…”
Section: Galt Deficiencymentioning
confidence: 99%